Chemotherapy response in primary peritoneal small cell carcinoma - Kholoud Alqasem; Sakhr Alshwayyat; Salsabeel Aljawabrah; Sundus Yahya Nser; Ala’aldin Eqleem; Mohammad Abu Shattal; Maisoon Hajir; Mohammed Al-mahdi Al-kurdi (Discover Oncology)
Abstract Background Small cell carcinoma (SCC) is a neuroendocrine tumor that usually originates in the lungs but can also arise from extrapulmonary sites. Extrapulmonary small cell carcinomas (EPSCCs) are aggressive and rare, with limited data guiding their management. This case report contributes to the literature by presenting the diagnosis and treatment of primary peritoneal SCC. Case presentation This case describes a 69-year-old man who presented with abdominal distension and pain, raising concerns for metastasis. He had a history of prostate cancer treated with radical prostatectomy and pelvic lymph node dissection. Biopsy and imaging revealed metastatic SCC involving the peritoneum and omentum. A diagnosis of primary peritoneal SCC or SCC of unknown primary origin was made due to the absence of a detectable primary tumor in typical sites. The patient underwent three separate courses of carboplatin/etoposide chemotherapy (6 cycles each), with each course resulting in significant disease regression and symptom relief. Recurrence was managed effectively with repeated chemotherapy cycles, but long-term follow-up showed the need for continued treatment to maintain disease control and quality of life. Conclusion This case underscores the importance of a multidisciplinary approach and patient-centered care in managing rare cancers like primary peritoneal SCC. Further research is essential to clarify its molecular characteristics and improve therapeutic options. Graphical abstract